Creating church online: ritual, community and new media - Hutchings, Tim (Routledge research in religion, media, and culture, 2017)
Welcome to the online church -- A brief history of cyberchurch -- Making sense of online churches -- Methodology: how to study an online church -- Church of fools -- I-church -- St Pixels -- The Anglican cathedral of second life -- Church online at lifechurch.tv -- Creating church online: media design and media logic -- Being church online: networks and existential terrains -- What happened to the online church?